Penerapan Algoritma Hybrid Pathfinding A* dan Boids untuk Game Pesawat Tempur - Firdaus Rahmat Prasetyo; Eriq M. Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The A* and Boids hybrid pathfinding algorithms can be used as a way of tracking the flying paths of aircraft games. In hybrid pathfinding, A* algorithm is used as the shortest path finding and avoid static obstacles while the Boids algorithm is used as a flyweeker in groups and avoids dynamic obstacles .Grid used for path search using A* algorithm is driven according to A* agent position that it does not increase number of nodes because in aircraft game the map size is so large. Pathfinding using A* algorithm will only be call when grid touch static obstacle, so pathfinding doesn't take a long time. This is proven when the agent uses an A* algorithm, the average of execution time increase by 4.24% and the average of FPS decreases by 11.59% compared with not using the A * algorithm. While the use of Boids algorithm is continuously on the aircraft so that the aircraft does not collide with each other. This algorithm is chosen because it has a time complexity that is not too high. This is also proven when there is dynamic obstacles in map, the average of execution time increase is only 6.21%.The average FPS on all maps is 75.91 which is above of the FPS limit that can trick the eye by 20. The average execution time of all maps is 102.79 ms. The average path length of all maps is 445.56. The average number of actors destroyed from all maps is 107.